Stability of SPEEK/Cloisite (R)/TAP nanocomposite membrane under Fenton reagent condition for direct methanol fuel cell application - Salleh, Muhammad Taufiq (Elsevier Science Ltd, 2017)
The stability of SPEEK/Cloisite (R)/triaminopyrimidine (SP/CL/TAP) nanocomposite membrane against radical attack during DMFC operation was elucidated by the Fenton reagent test. The nanocomposite membrane was soaked in the Fenton reagent solution with 0.8-50 ppm iron salts concentration for up to 96 h. The results indicate that presence of Cloisite (R) inorganic particles can improve the stability of SP/CL/TAP nanocomposite membrane against the radical attack. FF-IR characterization combined with DFT study has shown that C-O-C and -SO3H bonding with phenylene ring, and hydrogen bonding between SPEEK, Cloisite (R), and TAP are vulnerable to the radical attack. Loss of these functional groups has caused structural deformation, deterioration of mechanical strength, and changes of hydrophilicity in the SP/CL/TAP nanocomposite membrane. Additionally, changes in its chemical structure have caused its water uptake, proton conductivity, and methanol barrier properties to drop, up to 2 x higher than the Nafion (R) 117 membrane. However, the selectivity value of the SP/CL/TAP nanocomposite membrane (27,037 S.s/cm(3)) remains higher than the Nafion (R) 117 membrane (3292 S.s/cm(3)) due to its lower methanol permeability value (2.72 x 10(-7) cm(2)/s) as compared to Nafion (R) 117 membrane (2.95 x 10(-6) cm(2)/s). Based on the correlation graph, the SP/CL/TAP nanocomposite membrane could operate as PEM in the DMFC system up to 9800 h. Based on the results, it can be concluded that the SP/CL/TAP nanocomposite membrane has good stability in DMFC harsh environment and suitable to be employed as PEM for high-performance and long lifespan DMFC system.